2016
DOI: 10.1038/ncomms13362
|View full text |Cite
|
Sign up to set email alerts
|

CELF1 is a central node in post-transcriptional regulatory programmes underlying EMT

Abstract: The importance of translational regulation in tumour biology is increasingly appreciated. Here, we leverage polyribosomal profiling to prospectively define translational regulatory programs underlying epithelial-to-mesenchymal transition (EMT) in breast epithelial cells. We identify a group of ten translationally regulated drivers of EMT sharing a common GU-rich cis-element within the 3′-untranslated region (3′-UTR) of their mRNA. These cis-elements, necessary for the regulatory activity imparted by these 3′-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 68 publications
2
64
0
1
Order By: Relevance
“…Reciprocal coimmunoprecipitation experiments demonstrated that CELF1 interacts with eIF4E, and that this interaction is strengthened by eIF4E phosphorylation (Figure 3b). Indeed, translation of CELF1's previously defined EMT effector targets (10) was blocked in the S209A mutant expressing cells (Figure 3c-e), consistent with the notion that eIF4E phosphorylation is required for CELF1's function as a promoter of mRNA translation and EMT driver.…”
Section: Phosphorylation Of Eif4e Is Required For Celf1-driven Emt Insupporting
confidence: 82%
See 4 more Smart Citations
“…Reciprocal coimmunoprecipitation experiments demonstrated that CELF1 interacts with eIF4E, and that this interaction is strengthened by eIF4E phosphorylation (Figure 3b). Indeed, translation of CELF1's previously defined EMT effector targets (10) was blocked in the S209A mutant expressing cells (Figure 3c-e), consistent with the notion that eIF4E phosphorylation is required for CELF1's function as a promoter of mRNA translation and EMT driver.…”
Section: Phosphorylation Of Eif4e Is Required For Celf1-driven Emt Insupporting
confidence: 82%
“…Indeed, overexpression of the CELF1Δ365-371 (YAAAALP) mutant failed to induce EMT in MCF10A cells despite comparable levels of expression between the mutant and wild-type CELF1 proteins To determine whether the importance of the CELF1/eIF4E interaction was limited to EMT in vitro, we next assessed the importance of this interaction in a model of experimental metastasis. Overexpression of CELF1 induces experimental lung metastasis from the normally tumorigenic but non-metastatic MCF10AT1 cell line (10,34). Consistent with our own previously described work, ectopic expression of wild-type CELF1 within MCF10AT1 cells injected into the tail vein of nude mice conferred these cells with the ability to rapidly induce lung colonization in the animals tested.…”
Section: Interaction Of Celf1 and Eif4e Is Required For Celf1-driven mentioning
confidence: 99%
See 3 more Smart Citations